Antibacterial Activity of Surfactin Produced by Bacillus subtilis MSH1 - Mohd Hafez Mohd Isa; Mohammed Abdel-Hafiz Faisal Shannaq; Najwa Mohamed; Abdul Rahman Hassan; Najeeb Kaid Nasser Al-Shorgani; Aidil Abdul Hamid (Universiti Malaysia Sabah (UMS), 2024)
Non-Indexed Publication